THE UPRISING OF THE GULAN REVOLUTION IN BAHDINAN AND ITS OUTCOMES (1976–1978): A HISTORICAL STUDY - Taher, Hujeen; Tawfiq, Hoger (Humanities Journal of University of Zakho, 2025)
The Gulan Revolution uprising in Bahdinan is considered a significant event in Kurdish national history. After the collapse of the Aylol Revolution, the PDK made efforts on various levels to establish a temporary headquarters in the Bahdinan area in preparation for a new uprising. One of their first steps was to reorganize in villages and towns. They, then, set up a temporary headquarters, and during the establishment of their groups, they launched the revolution, initiating attacks in Sindi, Guli, northern Barwari, and Nerway. These attacks targeted Iraqi government military stations. Since Turkey adopted a policy of indifference, the revolution's focal point was Bahdinan. This research addresses several key questions: How did the PDK’s temporary headquarters help people recover from the fallout of the Aylol Revolution? Under these circumstances, how were they able to reorganize? How did they manage to re-establish their checkpoints? What steps did the PDK take to trigger the revolution? What strategies were used to secure its establishment? What was the Iraqi government’s response to the PDK’s groups? How did the Ba'ath government oppose the revolution and the Kurds?